Analisis Penggunaan E-Wallet Dalam Mempengaruhi Minat Beli Dikalangan Mahasiswa - Vivi Aulia Ramadhani; Ainun Mulyati; Haniyah Haniyah; Wahyu Hidayat; Zaini Ibrahim (Student Research Journal, 2024)
This research was created with the aim of knowing and analyzing the influence of product use and service features on students' interest in using e-wallets. The use of e-wallets is increasing and this has influenced the way consumers shop. In this article, we will discuss an analysis of the use of e-wallets in influencing buying interest. We will see how the use of e-wallets can influence the shopping behavior of individual consumers, as well as how this affects the sales industry as a whole. The results of the research we conducted show that the convenience, benefits and promotions provided by the e-wallet application play an important role in purchasing decisions or purchase interest among students at the Sultan Maulana Hasanuddin State Islamic University, Banten. This research approach uses a quantitative approach. The data used in this research is primary data obtained from questionnaires. The sample for this research consisted of students from the Sultan Maulana Hasanuddin State Islamic University, Banten, totaling 31 respondents. The analysis method uses regression test analysis.